Improvement process of partially cooked corn grit (PCCG) preparation - Sari, Anjar Ruspita; Abdul Rahman, Russly; Shukri, Radhiah; Hussain, Norhayati (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2019)
Steamed corn grits, or nasi jagung, is an indigenous, corn-based product, which is usually used to substitute rice, particularly in the central part of Java and Madura regions, Indonesia. However, there is limited information regarding the preparation of partially cooked corn grits (PCCG). The objective of the present work was therefore to compare the preparation of PCCG in terms of characteristics and time of preparation using optimised initial moisture content in the traditional process with optimised corn particle size, initial moisture content and processing temperature of the improved process. Water absorption index (WAI), water solubility index (WSI), yellowness index (YI), and resistant starch (RS) of dried PCCG, as well as textural properties of rehydrated PCCG, were compared between optimised PCCG prepared using traditional and improved processes to obtain the best PCCG. Results showed that the optimum initial moisture content to prepare PCCG by the traditional process was approximately 40%. The optimum conditions to prepare PCCG by the improved process were 300 μm corn particle size, 52.33% initial moisture content and 123.67°C processing temperature. PCCG prepared using the improved process had higher values of YI (99.51) and RS (3.65 g/100 g) but lower WAI value (3.74) than YI (95.78), RS (1.96 g/100 g) and WAI (3.96) of PCCG prepared using the traditional process. The textural properties of rehydrated PCCG, except for adhesiveness and cohesiveness, prepared using the improved process were not different from those of PCCG prepared using the traditional process. The improved process also had a shorter preparation time of PCCG, which was 4-6 h as compared to normally 3-4 d in the traditional process. Therefore, a more rapid process with more consistent qualities for preparing PCCG will be of benefit to the target population.